2007
DOI: 10.1292/jvms.69.177
|View full text |Cite
|
Sign up to set email alerts
|

Different Patterns of Vasoactive Intestinal Polypeptide (VIP)-Immunoreactive and Acetylcholinesterase (AChE)-Positive Innervation in the Internal Carotid Artery and Cerebral Arterial Tree of the Quail

Abstract: ABSTRACT. The innervation pattern of vasoactive intestinal polypeptide-immunoreactive (VIP-IR) nerves in the quail internal carotid artery (ICA) and cerebral arterial tree was investigated and compared with that of acetylcholinesterase-positive (AChE-P) nerves. The supply of VIP-IR nerves to the two arterial systems was distinctly richer than that of AChE-P nerves. It was focused mainly on the walls from the distal ICA to the caudal half of the anterior ramus (AR) through the cerebral carotid artery (CCA). Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…In rat, cerebral perivascular VIP-IR nerves reach a peak density at one month of age that is maintained until the fourth month [2,11]. The present study confirms and extends the previous observation that VIP-IR neuronal projection to the rAR from the CCA, which is an indication for mature pattern of the quail cerebrovascular VIP innervation [3], has been accomplished in most of the young birds aged P15. It has also shown that there is no appreciable statistical distinction in the nerve density of the corresponding major arteries of the anterior circulation among the four age groups from P15 to adulthood (P50).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In rat, cerebral perivascular VIP-IR nerves reach a peak density at one month of age that is maintained until the fourth month [2,11]. The present study confirms and extends the previous observation that VIP-IR neuronal projection to the rAR from the CCA, which is an indication for mature pattern of the quail cerebrovascular VIP innervation [3], has been accomplished in most of the young birds aged P15. It has also shown that there is no appreciable statistical distinction in the nerve density of the corresponding major arteries of the anterior circulation among the four age groups from P15 to adulthood (P50).…”
Section: Discussionsupporting
confidence: 90%
“…Recently, we have reported the unique pattern of cerebrovascular VIP-IR innervation in the adult Japanese quail that is distinctly different from the general mammalian pattern [3]. In this avian species, cerebral perivascular VIP-IR nerves have their major source at the same category of neurons in the nerve bundles accompanying the internal carotid artery (ICA) within the carotic canal, and mainly enter the cranial cavity through the cerebral carotid artery (CCA), the intracranial part of the ICA.…”
mentioning
confidence: 95%